DigiYatra – a digital experience for air travelers. Issue 2 (1st April 2022) - Heggde, Githa; Khanka, Sheetal; Damodaran, Akhil
Abstract : Learning outcomes: Students will learn technology strategies specific to airports. Students will understand the reason for the success of Bengaluru International Airport. Students will learn to apply management models in airport settings. Students will improve their understanding of airport business, airport-related technologies, specifically in the Indian settings. Case overview/Synopsis: DigiYatra is a revolutionary initiative by the Government of India to digitalize all the airports in India, making your face your boarding pass. Bengaluru International Airport Limited (BIAL) is at the forefront of this initiative. As one of the early public–private partnership airports, BIAL has seen many challenges over time but could succeed in all its endeavour. The case discusses the journey of DigiYatra, which BIAL has taken through the eyes of the Chairman, Hari Marar. The case goes through several layers like initial planning, creating the team, implementation challenges, technology strategy adopted and how they tackled Covid lockdown challenges to complete the project's initial phase. Complexity academic level: Post graduate students. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 11: Strategy.